SELF-CONFIDENCE IN EARLY CHILDHOOD: FAMILY COMMUNICATION DYSFUNCTION AND ITS IMPLICATIONS - Risti Agustina; Siti Khumayah; Aghnia Dian Lestari (Jurnal Komunikasi, 2026)
The quality of communication within the family plays a crucial role in shaping self-confidence in young children and can have a long-term impact. This study aims to identify types of family communication dysfunction, analyze their implications for the development of self-confidence, and explain the factors that shape self-confidence in young children. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation of five young children aged 6–12 years from diverse family backgrounds. This study concludes that there are five types of family communication dysfunction: lack of emotional responsiveness, rejection of children’s emotional expressions, the physical absence of parents as attachment figures, a shift in attention due to changes in family structure, and the substitution of affection with material fulfillment. Communication dysfunction leads to the formation of ambivalent and avoidant attachment patterns, withdrawal from social interaction, and the internalization of negative self-beliefs. Determinants of children’s self-confidence include the consistency of the attachment figure’s responses, emotional validation, the availability of a psychological secure base, emotional recovery after neglect, and the quality of substitute figures. These findings confirm that self-confidence in young children is strongly influenced by the warm and responsive emotional presence of parents.